A meta-analysis of the effects of nitrogen fertilizer application on maize (Zea mays L.) yield in Northwest China - Jiang, Yuanbo; Li, Haiyan; Ma, Wenqiong; Yu, Wenjing; Chen, Junxian; Gao, Yalin; Qi, Guangping; Yin, Minhua; Kang, Yanxia; Ma, Yanlin; Wang, Jinghai; Xu, Liting (Frontiers in Plant Science, 2025)
Nitrogen fertilizer application is an important method for the production of high-quality maize. However, nitrogen fertilizer addition patterns vary according to regional climate, field management practices, and soil conditions. In this study, a meta-analysis was used to quantify the yield effects of nitrogen addition on maize, and meta-regression analysis and a random forest model were used to study the main factors affecting the yield effects of nitrogen addition on maize. The results showed that nitrogen addition significantly increased maize yield by 50.26%–55.72%, and a fluctuating increasing trend was observed with the advancement of the experimental year. The increase in maize yield upon nitrogen addition was the highest in Gansu Province, and showed a decreasing trend with the rise in average annual temperature, but did not change significantly with the average annual precipitation. Among the field management factors, the increase in maize yield was better with the variety Qiangsheng 51, topdressing at the jointing and tasseling stages (JS, TS), nitrogen application rate of 175–225 kg·ha-1, and controlled release of nitrogen fertilizer and urea (CRNFU) or the application of a combination of organic and inorganic nitrogen (OIF). Moreover, the positive effects of nitrogen fertilizer application on maize yield improved with soil pH, organic matter, available potassium, available phosphorus, and total nitrogen content; decreased with soil carbon and nitrogen ratio and available nitrogen (AN) content; and were enhanced in chestnut soil, clay, and at a bulk density of 1.2–1.4 g·cm-3. Random forest model and multifactorial optimization revealed that the effects of nitrogen addition on maize yield in Northwest China were primarily influenced by experimental year, variety, soil type, AN, and soil pH.